2012
DOI: 10.1016/j.jval.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Antiviral Treatments for HBeAg-Positive Chronic Hepatitis B in Canada

Abstract: Tenofovir generated the best results compared with all other therapies under evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 53 publications
5
31
0
Order By: Relevance
“…They concluded that tenofovir is a cost-effective strategy compared with other options for CHB. Jinghe[33] using Markov modeling conducted a cost-effectiveness analysis of LVD, telbivudine, ETV and tenofovir for CHB in Canada and concluded that compared with other therapies tenofovir generated the best results. Bin Wu [34] evaluated the economic consequences of LVD, ETV, adefovir, and telbivudine for CHB treatment in China, and concluded that ETV is the most cost-effective option when treating both HBeAg-positive and HBeAg-negative CHB patients.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that tenofovir is a cost-effective strategy compared with other options for CHB. Jinghe[33] using Markov modeling conducted a cost-effectiveness analysis of LVD, telbivudine, ETV and tenofovir for CHB in Canada and concluded that compared with other therapies tenofovir generated the best results. Bin Wu [34] evaluated the economic consequences of LVD, ETV, adefovir, and telbivudine for CHB treatment in China, and concluded that ETV is the most cost-effective option when treating both HBeAg-positive and HBeAg-negative CHB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although guidelines recommend potent antivirals with a high barrier to resistance - entecavir and tenofovir - as first-line monotherapies, lamivudine is still one of the most preferred agents because of its inexpensive cost and excellent safety profile. Several studies from various countries have analyzed the cost-effectiveness of lamivudine and compared it with the other antiviral drugs [5,6,7,8]. They have all concluded that potent antivirals were much more cost effective than lamivudine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TDF is considered to have higher efficacy in Europe and America and has been recommended as one of the firstline treatments for CHB by several important associations dedicated to the study of the liver [5,9,10]. In developed countries some research indicates TDF may be the most cost-effective nucleos(t)ide treatment [11][12][13], mainly because of its low sale cost, excellent ability to suppress viral load, and the fact that no cases of virologic resistance have been observed. But whether TDF is also suitable for generalization for developing countries like China still remains uncertain.…”
Section: Introductionmentioning
confidence: 99%